Reconsidering Wagner’s law: evidence from the functions of the government - Afonso, António (2022)
We revisit Wagner’s law by function of government expenditure. Using data of 14 European countries between 1996 and 2013, we apply panel data and SUR methods to assess public expenditure–income elasticities. We find that some functions of government spending for a few countries (e.g. Austria, France, the Netherlands and Portugal) validate Wagner’s law. For the Netherlands, expenditures with environment protection increase more than proportionately to economic growth, and for France that is the case of spending in housing and community amenities. In addition, Greece is the only country where two public spending items react more than one to one to growth.